Clinical study of diabetic foot with different treatment modalities at Medical College Hospital Bikaner, Rajasthan, India - Thurwal, Kartik; Dawan, Manohar Lal; Parmar, Ashok (International Surgery Journal, 2017)
Background: Diabetes is a chronic disease. Diabetes the global epidemic is rapidly increasing at an alarming rate. Developing countries like India will harbour majority of diabetic people by the year 2030. Diabetic foot are complex, chronic wounds, which have a major long-term impact on the morbidity, mortality and quality of patients’ lives. Methods: Hospital based prospective study. From August 2015 to July 2016. 50 patients reporting to the General Surgery department within study duration and eligible as per inclusion criteria will be included in the study. Results: In present study, maximum 52% patients belonged to age group was 51-70 years followed by 13 (26%) in 31-50 age group. In present study most common complication of diabetes was cellulitis (32%) and least common complication was abscess (18%). In this study, most common lesion was right dorsum of foot 11 (22%) followed by left toe 7 (14%). Maximum 30% patients were treated through debridement of diabetic foot whereas 20% patients received slough excision, dressing and skin graft and toe amputation as treatment modality. 18% patients were treated by I and D. Amputation was the least used treatment modality. Conclusions: Diabetes mellitus is a lifelong disease and diabetic foot complications can be life threatening, physically incapacitating, costly to treat and result in extensive morbidity.